Experimental Research on Stability and Transition in High-Speed Wakes. Part 1. Research on the Transition Position in Supersonic and Hypersonic Wakes, and the Effects of Temperature and Other Factors - Lysenko, V.I. (Engineering Transactions, 2015)
The development of disturbances in a supersonic wake (free viscous layer and regular wake) behind a flat plate, both in linear and in nonlinear phases of development was investigated. The influence of several factors (Mach and Reynolds numbers, temperature factor, thickness of a plate, length of its stern) on the wake stability was studied.